Representing the Movement / Presenting the Movable - Herranz-Pascual, Yolanda; Pastor-Bravo, Jesús; Barreiro-Rodríguez, M. Covadonga (Arte, Individuo y Sociedad, 2013)
This article is proposed as an analysis of the artistic works which were interested in including movement representation or pointing to the attainment of kinetic art. Before incorporating the real movement in art works, there have been different attempts to represent it: by poses, instant grasp, or action narrative suggestion, and also by giving form to different movement stages. Thus, in this study we define two possible itineraries: “Representing the Movement” goes through the different approximations to movement representation from the pictorial and photographic practice, and “Presenting the Movable” does the same from the sculpture. We will travel through the path that covers the first trials to represent and fix something that moves in order to conquer the movable art itself, where the work becomes process and event, and it is developed, finally, into a time and space expanded action.